2019
DOI: 10.1093/infdis/jiz361
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Partial and Full Influenza Vaccination Among Children Aged <9 Years in Hong Kong, 2011–2019

Abstract: Background Two doses of influenza vaccination are recommended for previously unvaccinated children aged <9 years, and receipt of 1 dose is sometimes termed “partial vaccination.” We assessed the effectiveness of partial and full influenza vaccination in preventing influenza-associated hospitalization among children in Hong Kong. Methods Using the test-negative design we enrolled 23 187 children aged <9 years admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This finding is consistent with antibody immune response and limited observational studies o f b o t h o u t p at i e nt s a n d i n p at i e nt s i n t h e US a n d elsewhere. [20][21][22][23][24][25] Among partially vaccinated children overall, we detected statistically significant VE, which has been reported in fewer studies. 10,26,27 However, 1 dose of vaccine in the current season did not provide statistically significant protection against laboratory-confirmed influenza among the small proportion of previously unvaccinated children aged 2 years or younger.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with antibody immune response and limited observational studies o f b o t h o u t p at i e nt s a n d i n p at i e nt s i n t h e US a n d elsewhere. [20][21][22][23][24][25] Among partially vaccinated children overall, we detected statistically significant VE, which has been reported in fewer studies. 10,26,27 However, 1 dose of vaccine in the current season did not provide statistically significant protection against laboratory-confirmed influenza among the small proportion of previously unvaccinated children aged 2 years or younger.…”
Section: Discussionmentioning
confidence: 92%
“…Our study suggests a benefit of receiving 2 doses of inactivated influenza in the first season of vaccination as well as full vaccination as recommended by the ACIP. This finding is consistent with antibody immune response and limited observational studies of both outpatients and inpatients in the US and elsewhere . Among partially vaccinated children overall, we detected statistically significant VE, which has been reported in fewer studies .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the SPRs of a one-dose regimen in participants who had received two or more doses were comparable to those of a two-dose regimen in vaccineunprimed participants. A study in Hong Kong reported that the vaccine effectiveness induced by a one-or two-dose vaccination regimen was 73% and 31%, respectively, in children aged 6 months through 9 years receiving influenza vaccination for the first time [11]. Another effectiveness study in Japan revealed that both one-and two-dose regimens of IIV significantly reduced cases of any influenza among children aged 1-12 years; however, only the two-dose regimen was significantly effective in preventing influenza B in certain influenza seasons [12].…”
Section: Discussionmentioning
confidence: 99%
“…These two studies suggested that annual influenza vaccination is 40%-60% effective against LCI hospitalization in young children; however, the estimates included LAIVs and were not restricted to IIVs. More recent studies (146)(147)(148)(149)(150)(151) have rather found high VE rates against LCI hospitalization (up to 81%) in young children (Table 2).…”
Section: Vaccine Efficacy/effectiveness and Other Benefits Of Iivs In Children Under 5 Yearsmentioning
confidence: 92%